ANALYSIS OF USER RATINGS ON THE BUBBLE LYSN APPLICATION USING THE SYSTEM USABILITY SCALE (SUS) METHOD - Irna Syarifatul Aen; Meinarini Catur Utami (Indragiri Islamic University, 2023)
ABSTRACT Artists from the agency. In 2020 Dear U launched a bubble feature that can send messages between fans and artists in the form of text, video, photos, or voice notes with a live broadcast system where these messages will reach users who subscribe and vote for the artist they like. This feature also has an attractive appearance with two-way communication where users can also reply to messages sent by the artist. So this feature allows users and artists to feel closer to each other. This study aims to analyze the usability of the bubble lysn application based on the user's experience.